Factors Affecting Nursing Student Satisfaction in Online Learning During the COVID 19 Pandemic - Rohayati, Rohayati; Pradana, Anung Ahadi; Noerfitri, Noerfitri (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2022)
Introduction: The Covid-19 pandemic had an impact on nursing education in Indonesia. Most nursing education providers have not implemented online learning before the Covid-19 pandemic. All components of the campus must adapt quickly so that learning outcomes can be obtained as planned. This study aims to find out the factors that influence the satisfaction of nursing students in online learning.Method: This study uses a quantitative approach with a cross-sectional design. The population is 350 undergraduate nursing students in private nursing education. The response rate was 203 people (58%). Ethical clearance was conducted by the Etic Committee of Bani Saleh School Health Science with the number EC.181 / KEPK / STKBS / VIII / 2022. Data collection is carried out from August to September 2022. Data analysis using SPSS 24 using spearman rank. Results: The results showed that most respondents were female, with a median age of 22.78 years, and most were in regular programs. Most of the students had online learning experiences before the pandemic. The median hours of online study are 7.66 hours. The results of the bivariate analysis show that the variables that have a relationship with positive direction and moderate correlation with student satisfaction are student readiness (p-value 0.00; r 0.55); learning design (p-value 0.000; r 0.44), technology support (p-value 0.00; r 0.48); lecturer interaction (p-value 0.000; r 0.40). Variables that are related but have a positive direction with a weak correlation include the learning platform (p-value 0.000; r 0.30), social presence (p-value 0.000; r 0.26); direct instruction (p-value 0.000; r 0.26); student interaction (p-value 0.000; r 0.26) and learning content (p-value 0.000; r 0.30).Conclusions: All factors are related to student satisfaction in online learning. Factors that have a moderate correlation are student readiness, learner design, technology support, and lecturer interaction. Educational institutions must be proactive in reviewing online learning policies and conducting studies before implementing online learning methods.